RISK FACTORS FOR DEVELOPMENT OF OBSTETRIC BLEEDING AND THEIR SIGNIFICANCE (Archive of Conferences, 2020)
In economically developed and developing countries, obstetric hemorrhage is one of the leading causes of maternal morbidity and mortality. About 14 million women worldwide experience postpartum hemorrhage every year. A decrease in maternal mortality from obstetric bleeding is mainly associated with the identification and management of high-risk pregnant women, timely and complete correction in the hemostasis system, treatment of concomitant diseases, the introduction of new technologies, and adequate therapy in the postpartum period